Children's aspirations and perceptions of science learning beyond the teacher-led - BOATH, LAUREN ELIZABETH (Trinity College Dublin. School of Education. Discipline of Education, 2019)
Within this research study, a legally-robust children's rights-based methodology developed from the work of Lundy (2007) and Lundy and McEvoy (2011) was employed to explore children's perceptions of, and aspirations for, science learning beyond the teacher-led. Children were involved as coresearchers and research participants (subjects). They brought to the study expertise as children with contemporary experience in peer groups similar to 'people like them' (Murphy, Lundy, Emerson, & Kerr, 2013). Children in a Scottish primary school formed a Children's Research Advisory Group (CRAG). The remit of the CRAG included advising on how best to engage with other children on the issues being researched (Lundy & McEvoy, 2011), identifying themes to be explored within the research by providing insight on issues relating to the research questions, co-designing the research instrument (Murphy, Kerr, Lundy, & McEvoy, 2010), data analysis and evaluation, and reporting to research participants. Almost 1100 children aged 8-14, in 13 primary and secondary schools across five Scottish local authorities, were involved in either piloting a questionnaire or as research participants. This research study demonstrates that the children's rights-based methodology (Lundy, 2007; Lundy & McEvoy, 2011) can be employed successfully for a large-scale mixed-methods study relating to mainstream learning and teaching within the curriculum, in the Scottish context. An 'insider' view (Murphy, Mullaghy, & D'Arcy, 2016) leads to the content, language and design of the questionnaire being markedly different from those designed by adult researchers, resulting in high return rates and more robust data. This 'insider' view also provides insights in terms of understanding and interpreting responses and analysing and evaluating data. Children can engage as coresearchers, about matters beyond their lived experience, and demonstrate an understanding of the nuances and challenges of research. I propose the children's rights-based methodology employed within the research as an operationalisation of Vygotsky's cultural historical theory, through which zones of proximal development are created for children as coresearchers and research participants, adults as coresearchers and for the research itself. Children within the study overwhelmingly reported liking learning science in school. This is the case for research participants in primary and secondary school, with the male-female 'gender gap' evident only in strength of responses at age 13. Children who do not enjoy science learning beyond the teacher-led, do not necessarily dislike learning science in school. As children progress from primary to secondary school, they continue to report liking learning science in school. However, their enjoyment of visiting places to do with science declines, as does the percentage of those reporting science experiences beyond the teacher-led as 'fun' or 'interesting'. The CRAG participants expressed an expectation that, for children in secondary school, science experiences should be 'more educational' and 'less fun'. However, the evidence from this study is that secondary school participants are not having 'more educational' science experiences beyond the teacher-led. Whilst the majority of participants report finding science experiences fun, they do not consequently relate this to finding science fun. Fun is not an aspiration for science experiences for the majority of research participants. To a far greater extent, children are seeking the kind of enjoyment that comes from the challenges of learning, through interactivity and participation. Two underlying factors within children's science experiences were identified: external motivators relating to relevance, context and the wider world; internal motivators relating to fun, interest, curiosity and learning. The more positive children's self-perception of their science abilities, and the more they like learning science in school, the more likely they are to experience both the external motivators' and 'internal motivators' as a result of their science experiences. There is a sense of science experiences beyond the teacher-led 'preaching to the converted'. Lundy, L. (2007). 'Voice' is not enough: conceptualising Article 12 of the United Nations Convention on the Rights of the Child. British Educational Research Journal, 33(6), 927-942. doi:10.1080/01411920701657033 Lundy, L., & McEvoy, L. (2011). Children?s rights and research processes: Assisting children to (in)formed views. Childhood, 19(1), 1-16. doi:10.1177/0907568211409078 Murphy, C., Kerr, K., Lundy, L., & McEvoy, L. (2010). Attitudes of Children and Parents to Key Stage 2 Science Testing and Assessment: Final Report to the Wellcome Trust. Retrieved from Online: http://www.wellcome.ac.uk/stellent/groups/corporatesite/@msh_peda/documents/web_document/wtx062721.pdf Murphy, C., Lundy, L., Emerson, L., & Kerr, K. (2013). Children's perceptions of primary science assessment in England and Wales. British Educational Research Journal, 39(3), 585-606. doi:10.1080/01411926.2012.674921 Murphy, C., Mullaghy, M., & D'Arcy, A. (2016). 'Scientists are not always right, but they do their best.' Irish children's perspectives of innovations in science teaching and learning. School Science Review, 98(362), 55-65.
APPROVED
Keywords: science learning; science education; children's voice; children's rights; informal learning; zone of proximal development (ZPD); cultural-historical theory (CHT); Vygotsky; formal learning; children coresearchers; sociocultural theory; Curriculum for Excellence; fun; challenge; enjoyment